HELICOBACTER PYLORI: A POSSIBLE CONTRIBUTOR TO CHRONIC RHINOSINUSITIS AND NASAL POLYPOSIS - Nisha Chaudhary; Ankur Goyal; Rishabh Kaushik; Anil Pandey; Sonali Bandil (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Chronic rhinosinusitis (CRS) and nasal polyposis are prevalent conditions affecting millions globally, characterized by prolonged inflammation of the sinonasal mucosa. Historically, Helicobacter pylori (H. pylori) has been recognized primarily for its role in gastric disorders, particularly peptic ulcer disease and gastric cancer. The link between H. pylori and CRS is particularly intriguing. Chronic inflammation in the sinonasal cavity may share common pathways with gastric inflammation, including the involvement of immune dysregulation and microbial dysbiosis.Materials & Methods: A hospital based cross-sectional study was conducted in 60 study subjects. First study group of 30 patients who were diagnosed with CRS and scheduled for surgery and other control group of 30 patients who were admitted for Septoplasty. The GERD Questionnaire (GERD-Q) and Reflux Symptom Index (R.S.I) were used. DNA extraction from both case and control groups was conducted, followed by amplification of the Ure-A gene using polymerase chain reaction (PCR) with an automatic thermal cycler.Results: The study included 30 patients with chronic rhinosinusitis (CRS), comprising 19 patients (63.3%) with nasal polyps and 11 patients (36.7%) without nasal polyps. Among these patients, 14 (46.7%) tested positive for H. pylori, while 16 (53.3%) tested negative, Among the 14 patients, 14 tested positive for H. pylori, 11 being from CRS while rest 5 were from non-CRS group. The study group exhibited a significantly higher prevalence of GERD history (P = 0.006) and H. pylori infection (P = 0.041), while LPR showed no significant difference (P = 0.325). There were no significant differences between the two groups concerning sex, marital status, age, residence, or history of similar conditions.Conclusion: In conclusion, this study suggests that Helicobacter pylori may play a significant role in the pathogenesis of chronic rhinosinusitis and nasal polyposis, highlighting its potential as a contributing factor to chronic inflammation in the nasal mucosa.